EMPLOYEE RETENTION STRATEGY: ANALYSING THE INFLUENCE OF CAREER DEVELOPMENT, COMPENSATION, AND JOB SATISFACTION ON TURNOVER INTENTION (International Journal of Innovative Technologies in Economy, 2025)
Turnover intention is a major challenge in human resource management that can affect the stability and operational efficiency of an organisation. This research is focused on examining how career advancement, rewards, and job contentment influence the desire of workers to leave their jobs at PT Surya Toserba Jatiwangi. A quantitative approach was used with multiple regression method to test the relationship between these variables. Data was collected through surveys, questionnaires and interviews of 104 permanent employees with non-probability sampling technique with saturated sample approach. The results show that career development has no significant effect on turnover intention, while compensation and job satisfaction have a significant effect on employees' intention to leave the company. These findings indicate that effective employee retention strategies need to focus on improving compensation and job satisfaction to reduce turnover rates, while career development remains an important factor in the long run to maintain employee loyalty.